Nanoscale distribution of bioactive ligands on biomaterials regulates cell mechanosensing through translocation of actin into the nucleus - Xiaojing Liu; Man Zhang; Peng Wang; Kaikai Zheng; Xinlei Wang; Wenyan Xie; Xiaokai Pan; Runjia Shen; Ruili Liu; Jiandong Ding; Qiang Wei (Proceedings of the National Academy of Sciences, 2025)
Cells respond to adhesive ligands such as arginine-glycine-aspartate (RGD) through integrins, which regulates cellular activities via influencing cytoskeleton assembly. Herein, we report that the nanoscale distribution of active ligands on biomaterials regulates cells through not only cytoplasmic tension but also nuclear tension. This is particularly related to translocation of actin into nucleus and highlighted in our interpretation of an “abnormal” phenomenon that large RGD nanospacing (>70 nm) disassembles integrin clusters, inhibits cell adhesion, but promotes osteogenic differentiation of mesenchymal stem cells. Our studies reveal that the unstable adhesion at the 150 nm RGD distance increases actin dynamics, resulting in the nuclear translocation of globular (G) actin. The compartment polymerization of more G-actins to filamentous actins in nucleus increases nuclear tension, facilitating transcription activity and releasing calcium ions from the endoplasmic reticulum. This noncanonical mechanotransduction process sheds insight into mechanotransduction pertinent to cell–material interactions.